Brain fiction : self-deception and the riddle of confabulation - Hirstein, William (Philosophical psychopathology. Disorders in mind., 2005)
Includes information on amnesia, anosognosia, Anton's syndrome, autism, Capgras' syndrome, Cotard's syndrome, denial, emotion, Fregoli's syndrome, hypothalamus, Korsakoff's amnesia, Korsakoff's syndrome, limbic system, lying, memory, mirror image syndome, orbitofrontal cortex, etc.